Seller and buyer obligations and guarantee of its implementation in the trade law of Iran and Egypt - Sharafoddin Tabatabai, Saeed (2021)
The purpose of this article is to study the obligations of the parties to the law in Iran and Egypt and guarantee its implementation. The main question that has been proposed and examined in this regard is what are the obligations of the seller and the buyer in the law of Iran and Egypt? And how can the guarantee of its implementation be assessed in the law of the two countries? The present article is a descriptive-analytical and examines the question using the library method. The results of this research show that by concluding a series of obligations, the parties will be responsible which must be observed, which have the same view of these obligations in both laws; obligations such as delivery of price and cost are the delivery of both documents. Of course, there are differences in the guarantee of fulfillment of obligations and effects. In Iran law, unlike in Egypt law, the effects of termination appear from the time of the termination, not from the time of the contract, therefore, until the day of termination, the contractor leaves all his works so, the return of benefits is from the day of termination; another major difference is that in the case of Iran law, loss, defects or transfer of goods do not preclude termination, except in the case of discretion. What can be concluded is that in Egyptian law, the return of benefits is officially accepted, but the legislator in Iranian law has not explicitly commented on this.